Age and/or postmenopausal status as risk factors for pelvic organ prolapse development: systematic review with meta-analysis - Luiz Gustavo Oliveira Brito (2022)
Introduction and hypothesis: Age is named as a risk factor for pelvic organ prolapse (POP), despite not being the primary outcome for many observational studies. Postmenopausal status is another associated factor but has many confounders. We aimed to systematically review the role of age and/or postmenopausal status in POP development. Methods: Systematic review addressing age and hormones, more specifically by postmenopausal status, from inception to March 2020 in four databases (PubMed, Embase, WOS, Cochrane Library). Quality of evidence was classified by the ROBINS-I classification for non-randomized studies. Experimental studies, animal studies, studies linking age with recurrent POP and case series were excluded. Effect estimates were collected from adjusted odds ratio plus 95% confidence intervals. Significance level was 5%. A discussion exploring mechanistic factors was also included. Results: Nineteen studies (11 cross sectional, 6 cohort and 2 case control) were included for quantitative analysis. Only two studies presented a low overall risk of bias for age; most of the domains were of moderate risk. Every additional year was responsible for a 10% increase in the risk to develop POP (OR = 1.102 [1.021–1.190]; i2 = 80%, random analysis, p = 0.012). This trend was confirmed when age was dichotomized into a cutoff of 35 (p = 0.035) and 50 (p < 0.001) years. Although an increase in the risk for POP was noted in postmenopausal women, this did not reach statistical significance (OR = 2.080 [0.927–4.668], i2 = 0%, p = 0.076). Conclusion: Age is a risk factor for POP; postmenopausal status was not statistically associated with POP, prompting the need for further studies addressing this factor.